Let the church say amen - Petersen, David; Perkins, JoAnn; Perkins, Bobby; Perkins, Gail S.; Film Movement ([Fair Lawn, N.J.] : Film Movement ; Prince Frederick, Md. : Distributed by RB Publishing, 2005)
Blocks away from the Capitol and White House stands a tiny storefront church, endeavoring to combat the street violence, unemployment, and homelessness that threaten American families living in poverty. Over the course of a year, this feature-length documentary follows four church members as they work to fulfill their dreams for a better life.
Enhanced for widescreen TV (16x9).
Special features include: This month's short film: A stolen moment /dir. Audrey Cummings ; Highlights from the Film Movement Series.
Originally released as motion picture in 2004.
Rev. Dr. JoAnn Perkins, Rev. Bobby Perkins, Gail S. Perkins.
Not recommended for ages under 17.
DVD; region 1.
Keywords: African American churches -- Washington (D.C.); Cities and towns -- Religious aspects -- Christianity; Documentary films; Video recordings for hard of hearing people; Audiobooks